Transdisciplinary teaching and learning in a master’s program in urban agriculture - Gjøtterud, Sigrid; Holen, Rasa; Hvoslef-Eide, Trine (International journal of sustainability in higher education, 2025)
Purpose This study aims to explore transdisciplinary teaching and learning in a transdisciplinary master’s course in an urban agriculture master’s program. Design/methodology/approach An action research approach was used, applying qualitative methods, such as reflection notes, classroom dialogues, focus group discussions and interviews. Findings The students expressed high-level inter- and intrapersonal competencies and provided thorough insights into how they developed ideas across disciplines. However, the potential for collaborating with partners outside the university (case owners) was not fully exploited and needs further development. Originality/value The study constitutes a detailed example of the benefits and challenges of transdisciplinary teaching and learning, suggesting an integral education. It adds to the knowledge of how to develop academia further to facilitate competence for sustainable development.